Sports activity and changes in physical fitness of Polish children and adolescents: OSF study - Baj-Korpak, Joanna; Zaworski, Kamil; Stelmach, Marian J.; Lichograj, Piotr; Wochna, Marek (Frontiers in Pediatrics, 2022)
Background Physical activity promotion programs for children and adolescents should constitute the basis of any national health policy aiming to improve physical fitness, which is a significant health indicator in children, adolescents, adults as well as elderly persons. Methods The study included 1,230 children and adolescents aged 8–16 years (60.1% of girls) from Poland. Five hundred and twenty-seven persons covered by the survey (42.8%) participated in physical activity promotion called “Athletics for All!” (AFA) as an experimental group and 703 peers not participating in any forms of physical extra-curricular activities as a control group. Participants were measured for basic anthropometric parameters and body mass indices were calculated: Body Mass Index (BMI) and Ponderal Index (PI). Evaluation of physical fitness was made using the OSF Test (3 × 10 m shuttle run, standing broad jump, 1 kg medicine ball overhead throw, 4-min run). Comparative analysis between the experimental and control groups was carried out using the T-test for independent samples. Analysis of correlations between quantitative variables was performed with Pearson's r coefficient. Results Statistically significant differences in all the tests were noted between the experimental group (AFA) and the control group in favor of the former one. Taking into account reference ranges of BMI created according to the latest Polish norms, statistically significant differences were noted between the subgroups in all physical fitness tests. As far as PI is concerned, in the AFA group significant differences were noted in all physical fitness tests between subgroups created in accordance with the aforementioned norms. Conclusion The findings of our study show that it is necessary to introduce physical activity promotion programs for children and adolescents. Such programs should constitute the basis of national health policy aiming at improving physical fitness among young people.